2011
DOI: 10.1016/j.jhazmat.2010.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride adsorption studies on mixed-phase nano iron oxides prepared by surfactant mediation-precipitation technique

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Experimental procedure MaterialsFe(NO 3 ) 3 .7H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 31 publications
1
34
0
5
Order By: Relevance
“…Most of the FTIR studies on fluoride removal by different adsorbents have shown the involvement and the participation of the surface sites and potential functional groups in the adsorption, especially the hydroxyl group [138,139]. It was observed that fluoride interacts with the OH and NH groups on surface aluminum-impregnated coconut fiber surface [140].…”
Section: Fluoride (F − ) Adsorption Isotherm and Adsorption Capacitymentioning
confidence: 99%
“…Most of the FTIR studies on fluoride removal by different adsorbents have shown the involvement and the participation of the surface sites and potential functional groups in the adsorption, especially the hydroxyl group [138,139]. It was observed that fluoride interacts with the OH and NH groups on surface aluminum-impregnated coconut fiber surface [140].…”
Section: Fluoride (F − ) Adsorption Isotherm and Adsorption Capacitymentioning
confidence: 99%
“…However, sulfate and phosphate ions were found to compete with fluoride sorption on materials with iron and aluminum bases [13]. Chloride and sulfate interfered with fluoride removal by mixed-phase nano iron oxides [30]. All these experiments on the influence of other ions on sorption were done with synthetic fluoride solutions mixed with only single ion.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of chemical analysis and phase formation of various samples obtained by precipitation of iron oxides/hydroxides using similar conditions (i) in the absence of CTAB and magnesium [42], (ii) in the presence of CTAB [21], and (iii) in the presence of both CTAB as well as magnesium are given in Table 1.…”
Section: Tem Studiesmentioning
confidence: 99%
“…When precipitation was carried out by CTAB mediation in the absence of Mg(II) ions, mixed phases of iron oxides containing ferrihydrite, goethite, and hematite were obtained. Detailed studies on fluoride adsorption on the mixed oxides so obtained have been published [21] and will be compared in later section. It is only on surfactant mediation doping of Mg(II) ion hematite phase was formed.…”
Section: Tem Studiesmentioning
confidence: 99%
See 1 more Smart Citation